Principles of Inventory and Materials Management / Fourth Edition - Tersine J. Richard (Prentice Hall, 1994)
Preface, Introduction, Inventory, Types of Inventory, Organizational Categories and Inventory Problems, Functions of Inventory, Inventory Problem Classifications, Properties of Inventory, Inventory Costs, Cost Accumulation Profile, Conflicting Goals, The Inventory Flow Cycle, Financial Considerations, Product Positioning Strategies, Just-in-Time, Business Cycle Influence, Conclusion, Questions, Cases.
Preface, Introduction, Inventory, Types of Inventory, Organizational Categories and Inventory Problems, Functions of Inventory, Inventory Problem Classifications, Properties of Inventory, Inventory Costs, Cost Accumulation Profile, Conflicting Goals, The Inventory Flow Cycle, Financial Considerations, Product Positioning Strategies, Just-in-Time, Business Cycle Influence, Conclusion, Questions, Cases.